Development of a Closed-Loop Controller for an Arduino-Based DC Chopper using Proteus and LabVIEW - Mutmainnah, Mutmainnah; Buwarda, Sukriyah; Lutfi, Lutfi (Jurnal Teknologi Elekterika, 2024)
This research focuses on developing a DC-DC converter voltage regulation system using an Arduino microcontroller, addressing the instability inherent in renewable energy sources like solar panels and wind turbines. Utilizing Proteus and LabVIEW, the study employs a quantitative deductive approach to experimentally simulate and model the system over four months at the Control and Automation Laboratory of Politeknik ATI Makassar. Key challenges of conventional converters, including limited PWM flexibility, output stability, and ripple reduction, are addressed through a closed-loop control system with voltage feedback. The methodology involves extensive parameter calculations derived from literature review and expected testing scenarios to ensure precise component selection and system performance. Specific calculations guide the determination of minimum component values, facilitating the desired input and output voltage levels with minimal ripple. Simulation testing validates the system's effectiveness, demonstrating successful integration between LabVIEW and Proteus through additional library utilization. The resulting DC-DC converter voltage regulation system enables more robust control through Arduino microcontroller, enhancing stability and efficiency in renewable energy applications.